Principles of Reversal Burden of Proof in the Perspective of Indonesian Criminal Law and Islamic Law - Ahmad , Gunaldi; Rosyid, Maskur; Mudzhar, M. Atho; Ritonga, Mhd Rasid (Jurnal Hukum Islam, 2022)
The principles of criminal law in Indonesia and Islamic criminal law do not burden the defendant in proving. However, there have been changes to the reverse burden of proof system, especially in cases of corruption and money laundering. This article discusses the principle of reversed burden of proof in Indonesian criminal law and Islamic criminal law. The research method is juridical-normative with statutory, conceptual, and historical approaches. Sources of data using primary and secondary legal materials. The results of the study show that there are seven principles of reverse proof in criminal law in Indonesia, namely the principle of justice, the principle of utility, the principle of wealth, the principle of evaluating evidence, the principle of legality, the principle of invisible crime, and the principle of presumption of guilt. Meanwhile, the principles of proof are reversed in Islamic criminal law, namely: intention, justice, maqāṣid al-sharīah, and presumption of guilt. Reverse proof in Islamic criminal law is not only applied in cases of corruption and money laundering, but is applied to all ḥudūd, qiṣāṣ and ta'zīr crimes. The principle of intention only exists in the Islamic criminal law system, because it relates to the divine side.